Features of the Krivbas territory seismicity - Kendzera, O.V.; Pigulevskiy, P.G.; Andrushchenko, Yu.A. (Reports of the National Academy of Sciences of Ukraine, 2021)
The results of processing and a generalization of seismic events on the territory of the Kryvyi Rih iron ore basin (Kryvbas) for the period from 2011 till 2020 are presented. By the analysis of the records at stations of I.S. Subbotin Institute of Geophysics of the NAS of Ukraine and the spectrograms of seismic events recorded by digital seismic stations of the General Center of Seismological Controls of the State Center of Space Agency of Ukraine, we found that the most of local seismic events are represented by powerful industrial explosions in quarries and mines. During the period 2011–2020, the Ukrainian seismic stations recorded more than a thousand powerful industrial explosions with mb ≥ 1.0. The magnitude of the 11 most powerful explosions carried out in 2011-2020 in quarries and mines is in the range of 2.7-3.5. During the same period of time, 19 seismic events of the tectonic origin with mb = 2.1 ÷ 4.5 were registered in the Kryvbas region.